2005
DOI: 10.1002/hipo.20132
|View full text |Cite
|
Sign up to set email alerts
|

Responses of excitatory hippocampal synapses to natural stimulus patterns reveal a decrease in short‐term facilitation and increase in short‐term depression during postnatal development

Abstract: Schaffer collateral excitatory synapses onto CA1 pyramidal cells are subject to significant modulation by short-term plasticity. This presynaptic, history-dependent modulation of neurotransmitter release causes synaptic transmission to be sensitive to the frequency of the input. As a result, temporally irregular input patterns, such as those observed in vivo, produce synaptic responses over a very wide dynamic range that reflect a balance of short-term facilitation and short-term depression. The neonatal perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 87 publications
5
52
0
Order By: Relevance
“…Using these natural stimulus patterns, our lab has previously investigated developmental differences in short-term plasticity at Schaffer collateral synapses between juveniles and young adults (Dekay et al 2006). We found that the pattern of responses of Schaffer collateral synapses varied over a wide dynamic range in response to these temporally complex stimuli but was very reproducible from trial to trial for synapses at both ages (juveniles and young adults).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Using these natural stimulus patterns, our lab has previously investigated developmental differences in short-term plasticity at Schaffer collateral synapses between juveniles and young adults (Dekay et al 2006). We found that the pattern of responses of Schaffer collateral synapses varied over a wide dynamic range in response to these temporally complex stimuli but was very reproducible from trial to trial for synapses at both ages (juveniles and young adults).…”
Section: Introductionmentioning
confidence: 95%
“…This activity-dependent modulation of neurotransmitter release occurs on time scales of milliseconds to tens of seconds and causes the strength of synaptic transmission to depend on the recent history of use (reviewed in Zucker and Regehr 2002). At Schaffer collateral synapses, several studies have reported a decrease in a simple form of short-term plasticity, paired-pulse facilitation in slices from young adults compared with juveniles (Dekay et al 2006;Foster 1995, 1998b). In addition, our lab has shown a decrease in short-term depression in response to constant high-frequency trains in young adults versus juveniles (Dekay et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…stage (Dekay et al 2006) and recording temperature (Klyachko and Stevens 2006), which was part of the rationale underlying our decision to use adult mice, recordings at near-physiological temperatures, and stimulus patterns similar to the activity seen in vivo. We note that the relief of prepulse inhibition that underlies the results seen in Scheuber et al (2004) is steeply dependent on the duration of the depolarization, requiring a relatively slow spike waveform (Park and Dunlap 1998); one possible explanation for the discrepancy is that the faster kinetics of spiking at near-physiological temperatures may be unable to recruit this effect, allowing us to more cleanly assess other mechanisms by which each channel subtype contributes to synaptic dynamics.…”
Section: Discussionmentioning
confidence: 99%